2020
DOI: 10.1590/1983-1447.2020.20190373
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between multimorbidity and the outcome of the treatment for pulmonary tuberculosis

Abstract: ABSTRACT Objective: To analyze the influence of multimorbidity on the treatment outcome of new cases of pulmonary tuberculosis. Method: A population-based analytical study, using secondary data, collected from the database of the Notification Disease Information System, of new cases of pulmonary tuberculosis in the state of Rio Grande do Sul between 2013 and 2016. The relationship between multimorbidity and the outcome was analyzed with Multinomial Logistic Regression. Results: Multimorbidity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
2
12
0
1
Order By: Relevance
“…This is in line with a study that found increased risks of adverse outcomes with increasing number of comorbidities. [13]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in line with a study that found increased risks of adverse outcomes with increasing number of comorbidities. [13]…”
Section: Discussionmentioning
confidence: 99%
“…[9] In high-income countries (HICs) 30% of adults experience multimorbidity, and its prevalence is also increasing in low-and middle-income countries (LMICs), [10] where NCDs are on the rise [11] and CCDs such as HIV remain a major public health issue. [12] Multimorbidity represents a substantial burden for individuals, increasing their risk of adverse events, [13,14] and puts health systems under strain, [9] particularly in LMICs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies indicate that the presence of comorbidities in TB patients is associated with unfavorable outcomes of the TB treatment. 11 Therefore, the coexistence of certain non-communicable diseases with TB represent several health challenges, requiring a focus on multidisciplinary collaboration and integrated strategies, to accurately deal with this double burden of disease. 12 …”
Section: Introductionmentioning
confidence: 99%